Modelling and simulation of device to device based protocol for ultra-reliable low latency communication - Kshash, Abdullah Dawood (2019)
This research project is about the simulation of Device to Device (D2D) communication using MATLAB coding. The focus of system design is for Ultra- Reliable Low Latency Communication (URLLC) system. It is important to understand the D2D communication concept through coding. By doing this way, it helps to save cost, easy to analyse which parameters affect the outputs. Also, it is very convenient to study the system using a simulation model. The design of the D2D concept in this research can be divided into three parts. The first part is the graphical display of the network. The second is coding to compute the latency and identify which nodes are sending and not sending the packet. The third part is about the plotting of the graphs for the packets sent and received. Generally, the idea is to look for latency (delay) and understand why there is latency happen in the network. The results show that more packet sends by the nodes will cause high latency. This is because of the contention of access to the network.